2021
DOI: 10.1177/08968608211043411
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives of coping with automated peritoneal dialysis

Abstract: Background: Patients receiving peritoneal dialysis (PD) experience poor quality of life, depression, anxiety and lifestyle changes. Insights into how patients adjust to and cope with PD from a psychological perspective will aid care. Methods: Participants were recruited purposively through the Central Northern Adelaide Renal and Transplantation Service in South Australia. Ten patients receiving automated PD (APD) (5 females and 5 males) aged 31 to 77 years (M = 59.3) participated in a semi-structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…14 Another recent qualitative study suggests that professional psychological support may be helpful, especially during key disease milestones such as being diagnosed as 'end-stage' and following dialysis initiation. 19 In these and other studies, patient re-framing of their situation associated with coping ability.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…14 Another recent qualitative study suggests that professional psychological support may be helpful, especially during key disease milestones such as being diagnosed as 'end-stage' and following dialysis initiation. 19 In these and other studies, patient re-framing of their situation associated with coping ability.…”
Section: Discussionmentioning
confidence: 82%
“…Drain sluggishness and pain on the cycler, with alarms and sleep disturbances, have been previously reported. 19,23 Even so, clinically significant drain issues may be under appreciated. 24 In this sample, drain difficulties and pain were prevalent and problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that PD at home aided preservation of pre-illness identity, but resulted in the feelings of isolation and being misunderstood. 27 After intervention such as telemedicine, patients felt a greater sense of control, and achieved positive attitude. 28 In our study, the empowerment model of PBL health education could be another effective intervention to improve anxiety among PD patients.…”
mentioning
confidence: 99%
“…Identified by Duncanson et al’s (2021) 1 study ‘Patient Perspectives of Coping with Automated Peritoneal Dialysis’, the themes of the psychosocial challenges and coping responses among patients receiving automated peritoneal dialysis (APD) are relevant and valid. One of the themes identified in this interview study was Resigned Acceptance of kidney failure and PD, which helped patients cope with challenges and consequently they were adherent to treatment.…”
mentioning
confidence: 99%